How to balance the goals of urban planning and real estate? A view from above the parapets. (February 2022) - Kauko, Tom
Abstract: Despite being subject of many studies, the fields of urban planning and real estate are usually seen as incompatible in terms of their goals, even if the ingredients dealt with are much the same: the built environment. This viewpoint addresses some of these familiar concerns, and then suggests extended cooperation in the design process as a solution to overcome the disagreements. Potentially the result is a win-win situation. This argumentation also gives insight into how such mutual benefit is achievable by inviting corporate real estate interests to the negotiations about planning, and by using urban design for creating both quality and value in one and the same process. Highlights: The fields of urban planning and real estate are usually seen as incompatible interms of their goals, even if the ingredients dealt with are much the same: thebuilt environment. This viewpoint addresses some of these familiar concerns, and then suggests extendedcooperation in the design process as a solution to overcome the disagreements. Potentially the result is a win-win situation. This case study adds new insight into how such mutual benefit is achievable byinviting corporate real estate interests to the negotiations about planning, and by using urban design for creating both quality and value in one and thesame process.